Need for regulation of pan masala advertisements in television media - A Winnifred Christy; T Jones Raja Devathambi; B Deepikalakshmi (Wolters Kluwer Medknow Publications, 2021)
Tobacco industries have resorted to brand stretching to keep their brands visible through sale of non-tobacco products like elaichi (cardamom) and paan masala, as seen in television advertisements aired during Indian premier league matches. The direct and indirect forms of advertisements of tobacco products in digital media remains unchecked. Strict ban should be enforced as these advertisements lure children and the youth into consumption of tobacco products later in life. In addition to providing tobacco cessation services to patients, oral health professionals should be aware of the marketing strategies of tobacco companies so that we can advise governing authorities to enact new laws and enforce existing laws in order to curtail tobacco consumption in our country.